Generating a fluorescently tagged MARK2 fusion protein as a marker for the basolateral membrane of preimplantation stage mouse embryo blastomeres - Pezelj, Stefanie (Jihočeská univerzita, 2019)
The aim of this thesis was to develop a recombinant MARK2-fluorescent fusion protein construct to serve as a basolateral marker in future studies.
Generating a fluorescently tagged MARK2 fusion protein as a marker for the basolateral membrane of preimplantation stage mouse embryo blastomeres